(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The cross-sectional study explores the influence of physiological growth on Body Mass Index (BMI) in Pubescent. Baseline data of 475 students examined on BMI index were calculated. Both sexes exhibited high values of overweight and found to be advancing towards obesity with increasing age. This can be a matter of great concern as overweight aggravates not only physiological problems, but it may affect adversely on the self-concept of young children. Though, increase in height is very consistent between groups and children are found with very little progression in height. Researcher wants to find is there any association between emotional maturity and the puberty, it was studied in this paper this paper is an analytical study for finding the impact of physiological changes during the puberty.